Design of Improvement of the Existing UI/UX in the "Banyuwangi Tourism App" Application to Improve the Quality of Tourism Application in Banyuwangi Regency Using the Design Thinking Method - Wardhana, Adhika Aryasatya; Rumanti , Augustina Asih; Supratman, Nurdinintya Athari (eProceedings of Engineering, 2024)
Banyuwangi Regency has many promisingtourist destinations, including Ijen Crater as a natural tourismobject, Cacalan Beach as a marine tourism object, andGandrung Terracotta as a cultural tourism object which is anattraction for tourists to come to Banyuwangi Regency."Banyuwangi Tourism App" is an application launched byBanyuwangi Regency as a medium of information abouttourism in Banyuwangi Regency. This application providesinformation on tourist destinations in Banyuwangi Regency,Banyuwangi Festival information, information abouttraditional markets, and ordering food at traditional markets.However, users still experience problems using the application,based on the data obtained, users experience problemsregarding ticketing, completeness of information, systems, andUX. System design in this final project will use the designthinking method to design prototypes according to what the userneeds. This method consists of 5 stages, namely, Empathize,Define, Ideate, Prototype, Test. The results of this study are aprototype for improving the UI/UX using the design thinkingmethod to provide a more effective and efficient applicationdesign for improving the quality of tourism application in theBanyuwangi district. Keyword — Application, Application Improvement Design,Banyuwangi, <Banyuwangi Tourism App=, Design Thinking,System Improvement Design